AN X-RAY ABSORPTION FINE STRUCTURE SPECTROSCOPY STUDY OF GERMANIUM-ORGANIC LIGAND COMPLEXES IN AQUEOUS SOLUTION - Pokrovski G.S.; Martin F.; Hazemann J.L. (My University, 2000)
The local environment around Ge(IV) in 0.002 to 0.023 m aqueous solutions at ambient temperature was characterised as a function of pH and in the presence of different organic ligands (citric and oxalic acids, and catechol) using high resolution X-ray absorption fine structure spectroscopy (XAFS). Results show that both in organic-free solutions at acid to basic pH and in carboxylic acid-bearing solutions at neutral to basic pH and catechol-bearing solutions at acid pH, Ge is coordinated with four oxygens with mean Ge-O distances of 1.75+/-0.02 #9. This is consistent with the formation of the aqueous Ge(OH)4° and GeO(OH)3- complexes and confirms the results of previous studies based on solubility, potentiometry and Raman spectroscopy ([Pokrovski, G.S., Schott, J., 1998a. Thermodynamic properties of aqueous Ge(IV) hydroxide complexes from 25 to 350°C: implications for the behavior of germanium and the Ge/Si ratios in hydrothermal fluids. Geochim. Cosmochim. Acta 62, 1631-1642; Pokrovski, G.S., Schott, J., 1998b. Experimental study of the complexation of silicon and germanium with aqueous organic species: implications for Ge and Si transport and Ge/Si ratio in natural waters. Geochim. Cosmochim. Acta 62, 3413-3428]). By contrast, in carboxylic acid-bearing solutions at acid pH and in catechol-bearing solutions at pH>4 Ge is coordinated by 6 oxygen atoms with Ge-O distances ranging from 1.85 to 1.94 #9. This implies the formation of chelate type complexes with the organic ligands. These results are in agreement with germanium speciation scheme in organic-bearing solutions proposed by Pokrovski and Schott (1998b), and explain a stronger affinity of germanium, compared with silicon, to chelating organic compounds. The formation of Ge-organic acid complexes can lead to a significant increase of Ge/Si ratios in organic-rich fluids and should be taken into account when using these ratios measured in surficial waters and biogenic opals to estimate chemical-weathering intensity and Ge and Si global fluxes.
Keywords: GERMANIUM; AQUEOUS SPECIATION; X-RAY ABSORPTION FINE STRUCTURE (XAFS) SPECTROSCOPY; ORGANIC LIGANDS; CHELATES; DISSOLVED ORGANIC CARBON (DOC)